DiGVis: A system for comprehension and creation of directed graphs for the visually challenged - Syal, Poonam; Chatterji, Shantanu; Sardana, Harish Kumar (Universal access in the information society, 2016)
One of the major barriers for the social inclusion of blind persons is the limited access to graphics-based learning resources which are highly vision oriented. This paper presents a cost-effective tool which facilitates comprehension and creation of virtual directed graphs, such as flowcharts, using alternate modalities of audio and touch. It provides a physically accessible virtual spatial workspace and multimodal interface to non-visually represent directed graphs in interactive manner. The concept of spatial query is used to aid exploration and mental visualization through audio and tactile feedback. A unique aspect of the tool, named DiGVis, offers compatible representations of directed graphs for the sighted and non-sighted persons. A study with 28 visually challenged subjects indicates that the tool facilitates comprehension of layout and directional connectivity of elements in a virtual diagram. Further, in a pilot study, blind persons could independently comprehend a virtual flowchart layout and its logical steps. They were also able to create the flowchart data without sighted assistance using DiGVis. A comparison with sighted subjects using DiGVis for similar task demonstrates the effectiveness of the technique for inclusive education.